Diagnostic Significance of HRAS Mutations in Epithelial-Myoepithelial Carcinomas Exhibiting a Broad Histopathologic Spectrum. (July 2019) - Urano, Makoto; Nakaguro, Masato; Yamamoto, Yoshinari; Hirai, Hideaki; Tanigawa, Maki; Saigusa, Natsuki; Shimizu, Akira; Tsukahara, Kiyoaki; Tada, Yuichiro; Sakurai, Kouhei; Isomura, Madoka; Okumura, Yuki; et al.
Abstract : Epithelial-myoepithelial carcinoma (EMC) is a rare salivary gland tumor that is histologically characterized by biphasic tubular structures composed of inner ductal and outer clear myoepithelial cells. Because of its histologic variety, it is sometimes challenging to make an accurate diagnosis, and useful ancillary tests are essential for this purpose. We investigated 87 cases of EMC arising in the major and minor salivary glands and seromucinous glands in the nasal cavity or bronchus to describe the histologic features and mutation status of selected key oncogenes. Classic EMC accounted for 40.2% of all cases. Other cases showed various growth patterns and cytologic features in addition to the typical histology; cribriform patterns, a basaloid appearance, and sebaceous differentiation were relatively common (17.2% to 18.4%), whereas oncocytic/apocrine, papillary-cystic, double-clear, squamous, psammomatous, Verocay-like, and high-grade transformation were rare. HRAS mutations were found in 82.7% of EMCs and were concentrated in codon 61. There was no significant correlation between the HRAS mutation status and the histology. No EMC ex pleomorphic adenoma cases had HRAS mutations. PIK3CA and/or AKT1 mutations were the second most frequent mutations (20.7%, 6.5%, respectively) and almost always cooccurred with HRAS mutations. It is noteworthy that the HRAS mutation was not identified in any salivary gland tumor entities manifesting EMC-like features, including adenoid cystic carcinoma, pleomorphic adenoma, basal cell adenoma/adenocarcinoma, and myoepithelial carcinoma. We conclude that HRAS mutations are a frequent tumorigenic gene alteration in EMC, despite its histologic diversity. This study provides further insight into strategies for diagnosing EMC and discriminating it from its mimics. Abstract : Supplemental Digital Content is available in the text.